Comparing ethnobotanical knowledge of medicinal plants between community health workers and local experts in the “Mata da Paraíba” zone, northeastern Brazil - ANNE CAROLINE PAIVA MAIA; EZEQUIEL DA COSTA FERREIRA; CAMILLA MARQUES DE LUCENA; ANDRÉ DOS SANTOS SOUZA; DENISE DIAS DA CRUZ; REINALDO FARIAS PAIVA DE LUCENA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Paiva Maia AC, da Costa Ferreira E, Marques de Lucena C, dos Santos Souza A, Dias da Cruz D, Paiva de Lucena RF. 2021. Comparing ethnobotanical knowledge of medicinal plants between community health workers and local experts in the “Mata da Paraíba” zone, northeastern Brazil. Biodiversitas 22: 5606-5616. The use of medicinal plants is an old practice in a society that has been transmitted to this day, with local experts recognized in many communities and being encouraged through public policies. In Brazil, Community Health Agents (CHWs) can be important for the dissemination of this practice, due to their work with the Health System and the community. This study aimed to compare the knowledge of medicinal plants between CHWs and local experts in the community of Timbó, the municipality of Jacaraú (Paraíba, northeastern Brazil). Semi-structured interviews were conducted addressing local names of plants, their indications, parts used, and preparation methods. The data on the species local importance were analyzed through the use value (UV) and relative importance (RI) methods. Local experts cited more species than CHWs. There was great local importance of some species both among local specialists and among CHWs. However, some species were highlighted exclusively among local specialists. Decoction and infusion stood out among the preparation methods and leaf, flower, and seed were the most prominent parts used. The diseases treated with plants are mainly related to the respiratory and digestive systems. Our findings show a correspondence between the CHWs’ knowledge and local experts’ knowledge, which leads us to believe that experts and CHWs may be sharing the same local knowledge in the study community.